Residential Environment of Public Universities for the Students: Friendly or Hostile in the Context of Bangladesh? - Tajwar, Tahmid (Indonesian Journal of Education and Social Sciences, 2024)
This study is about the residential environment of public universities in Bangladesh. The main aim of the study is to know the existing situation of residential environment whether its friendly or hostile for the students in the context of Bangladesh. Total 70 respondents who are students from 8 public universities of Bangladesh were taken  by using purposive sampling method. Medical facility, meal services, Internet facility, room condition, educational environment at residence, political influence in seat distribution,  ragging and guest room culture, recreational facilities, sanitation system, democratic environment at hall and provosts - students mutual coordination were taken into consideration to understand the situation of residence in universities. The research is designed by quantitative method. Here the facts are explained which lead to make the state friendly or hostile for the respondents regarding residential environment of public universities. This paper aims to represent the scenario as well as contribute to national sector by suggesting the policymakers, university authorities to be informed in the areas of concern from the perspective of students through the statistical exhibition on the condition of the dormitories of public universities in Bangladesh.